2019
DOI: 10.1017/wet.2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Size Impact on Efficacy of a Dicamba-plus-Glyphosate Mixture

Abstract: Chemical weed control remains a widely used component of integrated weed management strategies because of its cost-effectiveness and rapid removal of crop pests. Additionally, dicamba-plus-glyphosate mixtures are a commonly recommended herbicide combination to combat herbicide resistance, specifically in recently commercially released dicamba-tolerant soybean and cotton. However, increased spray drift concerns and antagonistic interactions require that the application process be optimized to maximize biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…However, it was observed that similar sizes increased drift 12 . Droplet sizes close to 620 µm were recommended as weed control was maintained above 90% 12 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it was observed that similar sizes increased drift 12 . Droplet sizes close to 620 µm were recommended as weed control was maintained above 90% 12 .…”
Section: Introductionmentioning
confidence: 97%
“…Other researchers have also observed that dicamba and glyphosate mixture increased the presence of dicamba in air by 3 to 9 times, with a decrease occurring only at temperatures below 15 °C 11 . In another case, studying the efficacy of dicamba in relation to the droplet size, researchers found that 395 µm droplet size achieved better weed control than other droplet sizes 12 . However, it was observed that similar sizes increased drift 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smooth-term estimated degrees of freedom (EDF) and deviance explained values are shown in Table 3. A smooth-term EDF of 1 indicates minimum GAM model fluctuation and characterizes a linear model (Butts et al 2018(Butts et al , 2019a(Butts et al , 2019c. Deviance explained values provide a model-fitting estimation between predicted values and actual observations, with greater percentages representing an overall better model fit.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to herbicide application, 10 plants per plot were tagged at the soil surface for aboveground biomass evaluation. To facilitate evaluation of Palmer amaranth control in response to droplet size, plants were allowed to grow up to 15 cm (Butts et al 2018(Butts et al , 2019a(Butts et al , 2019c. Rulers were used to ensure that tagged plants did not exceed 15 cm in height.…”
Section: Data Collectionmentioning
confidence: 99%